ChemInform Abstract: Facile Synthesis of Spirocyclic Lactams from β‐Keto Carboxylic Acids. Issue 44 (15th October 2015) - Yang, Wei; Sun, Xianyu; Yu, Wenbo; Rai, Rachita; Deschamps, Jeffrey R.; Mitchell, Lauren A.; Jiang, Chao; MacKerell, Alexander D.; Xue, Fengtian
Abstract This one‐pot cascade reaction towards both spirocyclic and fused cyclic lactams involves a Curtius rearrangement and an intramolecular nucleophilic addition of the enol carbon to the isocyanate intermediate.